Performance Enhancement Of Ultra-Wideband Power Control Using Ranging And Narrowband Interference Mitigation - Saeed, Rashid Abdelhaleem (2008)

(untitled)
Power control is a critical parameter for the design and evaluation of ultra-wideband (UWB) based ad-hoc networks due to its distributed control nature and non-fixed topology. Since the ad-hoc networks are infrastructure-less only local information is available for each node to maintain the limited resources available in the network. In UWB indoor networks the main issues in power control are the channel gain fluctuations induced by dense multipath and interference arising from the narrowband systems. In this thesis we have introduced a joint UWB physical/ medium access control layer (PHY/MAC) design for direct-sequence-based UWB (DS-UWB) power control design by exploiting the high time resolution of the UWB signal for channel gain improvement and mitigates the narrowband interference to reduce bit error rate (BER) and so enhance the throughput.The fine time resolution of UWB signals enables high ranging estimation resolution, which leads to more accurate transmitted power control. However, in dense multipath fading an accurate ranging is a problematic due to non-line-of-sight (NLOS) propagation environments. In this thesis we propose a maximum likelihood algorithm enhanced with synchronization scheme to estimate the time delay of direct-path signal in NLOS multi-path fading environment and mean acquisition time. The algorithm is examined under various doublet Gaussian pulse widths and bit energy-noise ratio )(pT)(0NEb and gives lower ranging error (0.32m) compared to others (eg. CRLB is 0.84m). The closer the narrowband interference band to the centre frequency of the UWB signal, the more signal-to-interference-noise ratio degrades. In this thesis we discussed a mitigation approach by using the flexibility of the doublet Gaussian pulse generation, where a notched band is contributed in the pulse spectrum to avoid the narrowband interferer frequencies. In this case worldwide interoperability for microwave access (WIMAX) and wireless local area network (WLAN) are used. The results are compared with orthogonal frequency division multiplexing-based UWB (OFDM-UWB) before and after mitigation. It was observed that DS-UWB shows better performance after pulse adaptation (1dB better than cognospectrum). The performance of power control using the proposed ranging and pulse adaptation schemes is investigated for different number of nodes. It is seen that, bit error rate of 10-4 can be achieved for 20 users maintaining 14.2dB SINR. Also the same bit error rate can be achieved for bit error rate for SINR using 40 pulses per bit (). The results have been indicated that the proposed approach is able to achieve better BER (1.6 dB) and throughput (12% more for 40 users) than previous related research works. dB3.12sN